PENERAPAN KONSELING KELOMPOK UNTUK MENINGKATKAN KESEJAHTERAAN SUBYEKTIF WARGA BINAAN DI LAPAS KEROBOKAN - Wilani, N.M.A.; Fridari, I.G.A.D.; Suarya, L.M.K.S. (Buletin Udayana Mengabdi; Vol 23 No 2 (2024): Buletin Udayana Mengabdi, 2023)
The results of the initial situation analysis show that some of the inmates in the Kerobokan Prison need psychological assistance to increase life satisfaction or subjective well-being. High subjective well-being indicates that inmates have good life satisfaction. One of the activities that can be addressed to improve subjective well-being is cognitive-behavioral group counseling. As many as 20 inmates participated in group counseling activities. The results of the quantitative analysis did not find significant differences in the level of subjective well-being before and after the counseling activities. However, qualitatively, the participants stated that they felt cared for, supported and valued through the activities they carried out. The assisted residents hope that counseling activities can be carried out more frequently. The results of this activity imply that the provision of continuous psychological service assistance is still needed by inmates at the Kerobokan Prison. Keywords: Counseling, Subjective Well-Being, SWB, Kerobokan Prison, Prison Residents